Counsel on maintaining dental and oral health at the Al Madinah Integrated Islamic Elementary School community in Bogor Regency - Melaniwati, Melaniwati; Binartha, Ciptadhi Tri Oka; Dwidjayanti, Siti Chandra; Komala, Olivia Nauli; Livia, Florencia; Andrietta, Gracia; Dipankara, Jackson; Kardinal, Yessica Puspita (Community Empowerment, 2021)
The spread of COVID-19 cases in Indonesia has increased over time. The government urges people to take extra measures to prevent the spread of COVID-19 and maintaining dental and oral health is one of those measures that could help to prevent the transmission of COVID-19. People are taught personal dental and oral health practices as well as the necessary health protocols if they decide to visit a dental health facility. The purpose of this activity is to increase participant’s knowledge of the transmission of COVID-19 and how to maintain their dental and oral health. The method used involved measuring the level of knowledge before and after counseling. Furthermore, online counseling and training were provided through Zoom. The pre and post-test results from 88 participants showed that there was a significant increase in knowledge after counseling.